Study protocol: Evaluating the impact of a rural Australian primary health care service on rural health - Buykx Penny; Kinsman Leigh; Humphreys John S; Tham Rachel; Asaid Adel; Tuohey Kathy (BMC, 2011)
Abstract Background Rural communities throughout Australia are experiencing demographic ageing, increasing burden of chronic diseases, and de-population. Many are struggling to maintain viable health care services due to lack of infrastructure and workforce shortages. Hence, they face significant health disadvantages compared with urban regions. Primary health care yields the best health outcomes in situations characterised by limited resources. However, few rigorous longitudinal evaluations have been conducted to systematise them; assess their transferability; or assess sustainability amidst dynamic health policy environments. This paper describes the study protocol of a comprehensive longitudinal evaluation of a successful primary health care service in a small rural Australian community to assess its performance, sustainability, and responsiveness to changing community needs and health system requirements. Methods/Design The evaluation framework aims to examine the health service over a six-year period in terms of: (a) Structural domains (health service performance; sustainability; and quality of care); (b) Process domains (health service utilisation and satisfaction); and (c) Outcome domains (health behaviours, health outcomes and community viability). Significant international research guided the development of unambiguous reliable indicators for each domain that can be routinely and unobtrusively collected. Data are to be collected and analysed for trends from a range of sources: audits, community surveys, interviews and focus group discussions. Discussion This iterative evaluation framework and methodology aims to ensure the ongoing monitoring of service activity and health outcomes that allows researchers, providers and administrators to assess the extent to which health service objectives are met; the factors that helped or hindered achievements; what worked or did not work well and why; what aspects of the service could be improved and how; what benefits have been realised and for whom; the level of community satisfaction with the service; and the impact of a health service on community viability. While the need to reduce the rural-urban health service disparity in Australia is pressing, the evidence regarding how to move forward is inadequate. This comprehensive evaluation will add significant new knowledge regarding the characteristics associated with a sustainable rural primary health care service.